2005
DOI: 10.1074/jbc.m508063200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Characterization of Membrane Blebs Purified from Neisseria meningitidis Serogroup B

Abstract: Studies with purified aggregates of endotoxin have revealed the importance of lipopolysaccharide-binding protein (LBP)-dependent extraction and transfer of individual endotoxin molecules to CD14 in Toll-like receptor 4 (TLR4)-dependent cell activation. Endotoxin is normally embedded in the outer membrane of intact Gram-negative bacteria and shed membrane vesicles ("blebs"). However, the ability of LBP and CD14 to efficiently promote TLR4-dependent cell activation by membrane-associated endotoxin has not been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
138
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 61 publications
(70 reference statements)
4
138
1
1
Order By: Relevance
“…At the same time, co-culturing with S. enterica serovar Typhimurium was associated with increased b-lactamase levels and/or leakiness of the ampicillin-resistant E. coli cells in the presence of ampicillin. It is known that a variety of growing Gram-negative bacteria release membrane blebs (Katsui et al 1982;Kadurugamuwa & Beveridge 1997;Li et al 1998;Beveridge 1999;Post et al 2005). Such blebs are associated with abnormal in-growth of the outer membrane, and they typically appear around the septa during cell division.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, co-culturing with S. enterica serovar Typhimurium was associated with increased b-lactamase levels and/or leakiness of the ampicillin-resistant E. coli cells in the presence of ampicillin. It is known that a variety of growing Gram-negative bacteria release membrane blebs (Katsui et al 1982;Kadurugamuwa & Beveridge 1997;Li et al 1998;Beveridge 1999;Post et al 2005). Such blebs are associated with abnormal in-growth of the outer membrane, and they typically appear around the septa during cell division.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in stimulatory potency was not caused by an altered expression of Bvg Ϫ -regulated virulence factors and was shown to be dependent on the enzymatic activity of PagL. It is well established that purified LPS, on a molar basis, is biologically more active than LPS incorporated into membrane structures such as in bacterial cells, outer membrane vesicles, or liposomes (36,42). This can probably be explained by an increased accessibility of LPS in soluble aggregates for extraction and subsequent transfer by LBP/CD14 to the TLR4/MD-2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, by disturbing LPS-LPS interactions, e.g., by EDTA treatment (29), LPS can be released from the outer membrane into the external environment. In previous studies, it was shown that membrane-bound LPS has a lower proinflammatory cytokineinducing activity than soluble LPS aggregates (36,42), probably due to the better accessibility of LPS in soluble aggregates for extraction and subsequent transfer by LBP/CD14 to the TLR4/MD-2 complex. Deacylation of LPS could potentially weaken the LPS-LPS interactions, leading to increased release from the cells and counterbalancing the effect of the reduced endotoxic activity of the purified, deacylated LPS.…”
Section: Deacylation Of Lps Influences Its Release From B Pertussis mentioning
confidence: 99%
“…These proteins engage endotoxin in a series of sequential protein-endotoxin and protein-protein interactions (8). LBP catalyzes the transfer of LPS from bacterial membranes (10) or aggregates of purified LPS to CD-14 either in soluble form or membrane-bound via a glycosyl-phosphatidylinositol (GPI)-linked membrane anchor (11). Monomeric endotoxin:CD-14 complexes that are released are the preferred substrate form of endotoxin for MD-2, presented either in extracellular form (6,7) or membrane bound via association with TLR4 (9).…”
mentioning
confidence: 99%